Le théâtre, outil de praxis évolutionnaire des anarchistes parisiens de la Belle Époque ? - Camille Mayer (Cahiers d’histoire)
The Belle-Epoque anarchists’ use of theatre is often overlooked. Yet this literature offers rich perspectives to understand theories of libertarian aesthetic or the way activism and art were articulated in the anarchist political project of that period. This article intends to present arguments that were made in favour of theatre in one the most widely read anarchist newspapers between 1895 and 1914, namely Les Temps Nouveaux. It will show how theatrical activities organized by anarchist activists would create an anarchist evolutionary praxis.